PENGARUH KEBAKARAN HUTAN DAN LAHAN DI KALIMANTAN TERHADAP PENINGKATAN POLUSI UDARA BAGI NEGARA SEKITARNYA - Putri, Salsabila; Saputra, Cahya Dwi; Hotimah, Oot; Ali, Ilham (Jurnal Geografi, 2024)
This article is about the effect of forest fires in Kalimantan on increasing air pollution for surrounding countries. The problem of forest fires has become a national issue that is of serious concern to the government. This incident occurs repeatedly every year, especially on the island of Kalimantan. Indonesia has very extensive and dense tropical forests, especially in the Papua and Kalimantan regions. These forests contribute significantly to oxygen production and carbon dioxide storage, which are important factors in maintaining global climate balance. Some people in Indonesia depend directly or indirectly on forests to earn a living and meet their daily needs. Air pollution due to forest fires in Indonesia does not only impact local areas, but can also spread to neighboring countries such as Malaysia, Singapore and Brunei. This can worsen the air quality and health of the citizens of these countries.